2006
DOI: 10.1073/pnas.0600914103
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of dynein to the Jurkat immunological synapse

Abstract: Binding of T cells to antigen-presenting cells leads to the formation of the immunological synapse, translocation of the microtubuleorganizing center (MTOC) to the synapse, and focused secretion of effector molecules. Here, we show that upon activation of Jurkat cells microtubules project from the MTOC to a ring of the scaffolding protein ADAP, localized at the synapse. Loss of ADAP, but not lymphocyte function-associated antigen 1, leads to a severe defect in MTOC polarization at the immunological synapse. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
212
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(217 citation statements)
references
References 28 publications
3
212
2
Order By: Relevance
“…A functional connection between kinesin, a microtubule plus-end directed motor, and JNK activity has been reported (24). Moreover, dynein has been shown to be involved in MTOC polarization (25). ERK2 and JNK1 signals may synergize to modulate the motor activities of kinesin and dynein molecules through phosphorylation, or they may work in parallel, each targeting some critical step during MTOC polarization.…”
Section: Discussionmentioning
confidence: 99%
“…A functional connection between kinesin, a microtubule plus-end directed motor, and JNK activity has been reported (24). Moreover, dynein has been shown to be involved in MTOC polarization (25). ERK2 and JNK1 signals may synergize to modulate the motor activities of kinesin and dynein molecules through phosphorylation, or they may work in parallel, each targeting some critical step during MTOC polarization.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells are more easily trapped in long-lasting (>30 min) interactions, decreasing availability for sequential target cell interactions. Stable interface actin accumulation could impair killing by preventing repolarization toward secondary targets, as dynein motors associated with the peripheral actin ring are used to position the microtubule organizing center (MTOC) at the cytolytic effector/target cell interface (30). In addition, long lasting NK cell/target cell couples did not lead to target cell lysis, thus further diminishing killing at the population level.…”
Section: Discussionmentioning
confidence: 99%
“…While diffusion could mediate this effect (e.g., in the context of a binding-protein gradient), the finding suggested that stimulated NF-B might use active transport. Brain NF-B has been reported to coimmunoprecipitate dynein intermediate chain and components of dynactin in the presence of cross-linkers (10), and dynein is also concentrated at the postsynaptic density in neurons (23) and recruited to the immunological synapse in T cells (24), both sites which can signal NF-B activation. We have now shown that NF-B nuclear transport following stimulation depends upon the dynein molecular motor.…”
Section: Discussionmentioning
confidence: 99%